Aspectos procesales para el procesamiento de los delitos de desapariciones involuntarias en el Ecuador. - Armas, Johselin A. (2022)
In the present investigation, a phenomenon that has legal and social importance is addressed, due to the fact that at present there has been an alarming increase in disappearances in Ecuador of which public opinion and the media have denounced socially, since Most of these have not been resolved after several years have elapsed, one of the limitations being precisely that Ecuador does not have a substantive criminal legal framework and, above all, an adequate procedural framework to be able to adequately investigate, prosecute, and punish these actions. that seriously injure the victims, considering this term in a broad sense, that is, not only the passive subjects of the offense, but above all the family and friends of the victims, who face a desperate situation due to the loss of relatives. For this reason, the investigation starts from the object of determining why the Comprehensive Criminal Organic Code does not regulate the procedural aspects for the prosecution of the crimes of involuntary disappearances in Ecuador.